CRISPLD2 Gene Polymorphisms with Nonsyndromic Cleft Lip Palate in Indian Population - Neela, Praveen Kumar; Gosla, Srinivas Reddy; Husain, Akhter; Mohan, Vasavi (Global Medical Genetics, 2020)
Cleft lip palate (CLP) is one of the common congenital anomalies with multifactorial etiology. Many genes are associated with its etiology. In one of the studies CRISPLD2 gene polymorphisms rs1546124, rs4783099, and rs16974880 were reported in the Chinese population. However, its role in the Indian population is not yet studied. Hence, this research was conducted on the Indian population to know the role of these high-risk polymorphisms in patients with nonsyndromic CLP. Following an inclusion and exclusion criteria, 20 multiplex CLP families were selected from a high volume cleft center in India. Genomic DNA was isolated from these families. Single nucleotide polymorphism (SNP) rs1546124, rs4783099, and rs16974880 were analyzed for their association using MassARRAY method. A whole-genome association analysis toolset, PLINK was used for statistical analysis. The polymorphisms followed Hardy–Weinberg equilibrium. None of the polymorphisms showed any significance. Hence the high-risk polymorphisms rs1546124, rs4783099, and rs16974880 are not associated with nonsyndromic CLP in Indian population.
Keywords: cleft lip palate; gene; polymorphism; CRISPLD2; MassARRAY